Thermodynamic effects in morphological evolution of polymer-fullerene nanocomposites for photovoltaic applications - Bernardo, Gabriel (2011)
Polymer based photovoltaic devices promise solar technologies that are inexpensive enough to be widely exploited and therefore provide a significant fraction of the future energy needs. There are many promising polymer-fullerene mixtures that are promising materials candidates for achieving high performance devices, but their exploitation requires and improved understanding of their structure-property relationships. Of particular relevance is the phase behavior of the mixtures. The phase behavior of donor-acceptor materials for photovoltaic applications is of key importance [1,2]: i) to gain a fundamental understanding and control of morphology development in the donor-acceptor blends; ii) to appropriately choose the operating window for thermal annealing; iii) to understand the long-term stability of the blended film morphology and consequently of the photovoltaic performance of the corresponding solar cells. In this work the phase behavior of polymer-fullerene mixtures is being studied using Differential Scanning Calorimetry (DSC), Wide-Angle X-Ray Scattering (WAXS), Small-Angle Neutron Scattering (SANS) and theoretical ab initio Density Functional Theory (DFT) calculations.